Role of mitochondrial ATP-sensitive potassium channel-mediated PKC-ε in delayed protection against myocardial ischemia/reperfusion injury in isolated hearts of sevoflurane-preconditioned rats - Wang,C. (2015)
This study aimed to determine the role of mitochondrial adenosine triphosphate-sensitive potassium (mitoKATP) channels and protein kinase C (PKC)-ε in the delayed protective effects of sevoflurane preconditioning using Langendorff isolated heart perfusion models. Fifty-four isolated perfused rat hearts were randomly divided into 6 groups (n=9). The rats were exposed for 60 min to 2.5% sevoflurane (the second window of protection group, SWOP group) or 33% oxygen inhalation (I/R group) 24 h before coronary occlusion. The control group (CON) and the sevoflurane group (SEVO) group were exposed to 33% oxygen and 2.5% sevoflurane for 60 min, respectively, without coronary occlusion. The mitoKATP channel inhibitor 5-hydroxydecanoate (5-HD) was given 30 min before sevoflurane preconditioning (5-HD+SWOP group). Cardiac function indices, infarct sizes, serum cardiac troponin I (cTnI) concentrations, and the expression levels of phosphorylated PKC-ε (p-PKC-ε) and caspase-8 were measured. Cardiac function was unchanged, p-PKC-ε expression was upregulated, caspase-8 expression was downregulated, cTnI concentrations were decreased, and the infarcts were significantly smaller (P<0.05) in the SWOP group compared with the I/R group. Cardiac function was worse, p-PKC-ε expression was downregulated, caspase-8 expression was upregulated, cTnI concentration was increased and infarcts were larger in the 5-HD+SWOP group (P<0.05) compared with the SWOP group. The results suggest that mitoKATP channels are involved in the myocardial protective effects of sevoflurane in preconditioning against I/R injury, by regulating PKC-ε phosphorylation before ischemia, and by downregulating caspase-8 during reperfusion.